PERANCANGAN ULANG ANTAR MUKA WEBSITE SEBAGAI MEDIA INFORMASI PERGURUAN TINGGI UNIVERSITAS TELKOM - MOCHAMMAD FAIZAL; ANDREAS RIO ADRIYANTO (Serat Rupa: Journal of Design, 2018)
Today, technology develops rapidly, where people can not be separated from the internet. In the internet, known a media named website, and ideally the Telkom University should implement the use of website to support various activities that take place in it, because it supports the vision of the Telkom University to be a "world class university". However, after a preliminary investigation, it has emerged some problems on the website of the Telkom University in terms of user interface and user experience, especially on mobile version. These things become important, because internet becomes a means to obtain information related to the higher education. To answer these problems, there will be activities redesign based on the data obtained through literature studies related to relevant theories, visual object observation from some similar websites, interviews with UI/UX experts, as well as distributing questionnaires to the target audience of the website itself. Once the data is collected, it will be analyzed through comparative matrix to obtain results that can be the basis of the interface redesign. Hopefully, with the user interface redesign of the Telkom University website will achieve a good user experience, and also bring a good image of the university itself.Â Keywords: media; UI; university; UX; website